DNA Methylation-Based Interferon Scores Associate With Sub-Phenotypes in Primary Sjögren’s Syndrome - Imgenberg-Kreuz, Juliana; Sandling, Johanna K.; Norheim, Katrine Brække; Johnsen, Svein Joar Auglænd; Omdal, Roald; Syvänen, Ann-Christine; Svenungsson, Elisabet; Rönnblom, Lars; Eloranta, Maija-Leena; Nordmark, Gunnel (Frontiers in Immunology, 2021)
Primary Sjögren’s syndrome is an autoimmune inflammatory disease with profound clinical heterogeneity, where excessive activation of the type I interferon (IFN) system is considered one of the key mechanisms in disease pathogenesis. Here we present a DNA methylation-based IFN system activation score (DNAm IFN score) and investigate its potential associations with sub-phenotypes of pSS. The study comprised 100 Swedish patients with pSS and 587 Swedish controls. For replication, 48 patients with pSS from Stavanger, Norway, were included. IFN scores were calculated from DNA methylation levels at the IFN-induced genes RSAD2, IFTM1 and IFI44L. A high DNAm IFN score, defined as > meancontrols +2SDcontrols (IFN score >4.4), was observed in 59% of pSS patients and in 4% of controls (p=1.3x10-35). Patients with a high DNAm IFN score were on average seven years younger at symptom onset (p=0.017) and at diagnosis (p=3x10-3). The DNAm IFN score levels were significantly higher in pSS positive for both SSA and SSB antibodies compared to SSA/SSB negative patients (pdiscovery=1.9x10-8, preplication=7.8x10-4). In patients positive for both SSA subtypes Ro52 and Ro60, an increased score was identified compared to single positive patients (p=0.022). Analysing the discovery and replication cohorts together, elevated DNAm IFN scores were observed in pSS with hypergammaglobulinemia (p=2x10-8) and low C4 (p=1.5x10-3) compared to patients without these manifestations. Patients < 70 years with ongoing lymphoma at DNA sampling or lymphoma at follow-up (n=7), presented an increased DNAm IFN score compared to pSS without lymphoma (p=0.025). In conclusion, the DNAm-based IFN score is a promising alternative to mRNA-based scores for identification of patients with activation of the IFN system and may be applied for patient stratification guiding treatment decisions, monitoring and inclusion in clinical trials.